Self-reported gingivitis and tooth loss poorly predict C-reactive protein levels: a study among Finnish young adults - Pekka V. Ylo¨ stalo (Blackwell Synergy, 2008)
Objectives: Our aim in this cross-sectional study was to investigate whether self-reported gingivitis and tooth loss were associated with elevated levels of C-reactive protein (CRP) using the same study population where these dental conditions have earlier been associated with prevalent angina pectoris. Material and Methods: The study population consisted of those Northern Finland birth cohort 1966 members who lived in Northern Finland or in the Helsinki region (n58463) at the time of the survey (1996–1997). The participation rate in a health examination was 71% (n56033). Gingivitis and tooth loss were determined on the basis of self-reported questions. Prevalence proportion ratios (PPR) and 95% confidence intervals (CI) were estimated using multivariate regression models. Results: The results showed that self-reported gingivitis and tooth loss were weakly associated with elevated levels of CRP (43 mg/l): adjusted PPR 1.1, CI 1.0–1.3 and PPR 1.1, CI 0.7–1.7, respectively. The proportion of variation in CRP explained by self-reported gingivitis and tooth loss was small, being o1%. Conclusion: The results suggest that self-reported gingivitis and tooth loss have a miniscule effect on CRP levels among a general population of young adults.